Tomassetti's masculinity. Issue 1 (1st March 2019) - Quinn, Hannah
In our current society women are increasingly being accepted as both creators and consumers. In the face of female empowerment, we must be willing to re-examine our relationship to masculinity. As women are no longer seen as 'lacking', there is an increasing call for men to be allowed to embody traditionally feminine traits. Written through the lens of psychoanalysis, this article examines the way in which the artist Alessandro Tomassetti subverts our expectations of masculinity in his painting of a young man in a lace glove titled The Big Time (2015).